MicroRNA-513b-5p targets COL1A1 and COL1A2 associated with the formation and rupture of intracranial aneurysm - Zheng Zheng (Nature Portfolio, 2021)
Abstract Collagen-type I alpha 1 chain (COL1A1) and COL1A2 are abnormally expressed in intracranial aneurysm (IA), but their mechanism of action remains unclear. This study was performed to investigate the mechanism of COL1A1 and COL1A2 affecting the occurrence and rupture of IA. Quantitative real-time polymerase chain reaction was used to measure the expression of hsa-miR-513b-5p, COL1A1, COL1A2, TNF-α, IL-6, MMP2, MMP3, MMP9 and TIMP4 in patients with ruptured IA (RA) (n = 100), patients with un-ruptured IA (UA) (n = 100), and controls (n = 100). Then, human vascular smooth muscle cells (HASMCs) were cultured, and dual luciferase reporter assay was performed to analyse the targeting relationship between miR-513b-5p and COL1A1 or COL1A2. The effects of the miR-513b-5p mimic and inhibitor on the proliferation, apoptosis, and death of HASMC and the RIP1-RIP3-MLKL and matrix metalloproteinase pathways were also explored. The effect of silencing and over-expression of COL1A1 and COL1A2 on the role of miR-513b-5p were also evaluated. Finally, the effects of TNF-α on miR-513b-5p targeting COL1A1 and COL1A2 were tested. Compared with those in the control group, the serum mRNA levels of miR-513b-5p, IL-6 and TIMP4 were significantly decreased in the RA and UA groups, but COL1A1, COL1A2, TNF-α, IL-1β, MMP2, MMP3 and MMP9 were significantly increased (p < 0.05). Compared with those in the UA group, the expression of COL1A1, COL1A2, TNF-α, IL-1β and MMP9 was significantly up-regulated in the RA group (p < 0.05). Results from the luciferase reporter assay showed that COL1A1 and COL1A were the direct targets of miR-513b-5p. Further studies demonstrated that miR-513b-5p targeted COL1A1/2 to regulate the RIP1-RIP3-MLKL and MMP pathways, thereby enhancing cell death and apoptosis. Over-expression of COL1A1 or COL1A2, rather than silencing COL1A1/2, could improve the inhibitory effect of miR-513b-5p on cell activity by regulating the RIP1-RIP3-MLKL and MMP pathways. Furthermore, over-expression of miR-513b-5p and/or silencing COL1A1/2 inhibited the TNF-α-induced cell proliferation and enhanced the TNF-α-induced cell death and apoptosis. The mechanism may be related to the inhibition of collagen I and TIMP4 expression and promotion of the expression of RIP1, p-RIP1, p-RIP3, p-MLKL, MMP2 and MMP9. MiR-513b-5p targeted the inhibition of COL1A1/2 expression and affected HASMC viability and extracellular mechanism remodelling by regulating the RIP1-RIP3-MLKL and MMP pathways. This process might be involved in the formation and rupture of IA.